Application of person–organization fit to military veterans - Meliza Figueroa-Torres; Josh Jordan; Michael J. Kirchner (Organization Management Journal)
Purpose – Human resource management professionals strive to establish a high person–organization (PO) fit when hiring, as doing so ultimately reduces turnover and increases employee performance outcomes. However, tailored strategies toward improving the PO fit of military veterans have yet to be explored – a particularly concerning oversight considering the prevalence of veteran hiring initiatives and correspondingly high turnover rates of former servicemembers in their first nonmilitary jobs. This paper aims to explore the PO fit model’s application toward military veterans in nonmilitary organizations. Design/methodology/approach – A review of veteran transition literature was conducted to identify aspects of military veteran career transition issues, which suggested a perceived gap in fit between their job or organization. Findings – The review revealed prevailing transition challenges which likely arose, at least in part, due to veterans’ lack of fit in nonmilitary organizations. The findings informed development of a veteran–organization fit model based on a needs-supplies conceptualization of PO fit. Research limitations/implications – The authors apply the needs-supplies perspective of PO fit to address identified veteran career transition challenges. Importantly, the authors offer organization management scholars concrete steps for assessing the impact of integrating the proposed framework within civilian organizations. Practical implications – This study sheds light on how PO fit practices can be tailored and integrated by HR professionals for their military veteran newcomers. The authors offer HR practitioners POF strategies for military veteran newcomers in nonmilitary organizations. Originality/value – This paper offers organization management and HR scholars and practitioners a needs-supply informed approach toward improving PO fit of military veteran newcomers.